A low FODMAP diet is associated with changes in the microbiota and reduction in breath hydrogen but not colonic volume in healthy subjects. - Tim J Sloan; Jonna Jalanka; Giles A D Major; Shanthi Krishnasamy; Sue Pritchard; Salah Abdelrazig; Katri Korpela; Gulzar Singh; Claire Mulvenna; Caroline L Hoad; Luca Marciani; David A Barrett; et al. (PLoS ONE)
Background & aims Ingestion of poorly digested, fermentable carbohydrates (fermentable oligo-, di-, mono-saccharides and polyols; FODMAPs) have been implicated in exacerbating intestinal symptoms and the reduction of intake with symptom alleviation. Restricting FODMAP intake is believed to relieve colonic distension by reducing colonic fermentation but this has not been previously directly assessed. We performed a randomised controlled trial comparing the effect of a low FODMAP diet combined with either maltodextrin or oligofructose on colonic contents, metabolites and microbiota. Methods A parallel randomised controlled trial in healthy adults (n = 37). All subjects followed a low FODMAP diet for a week and supplemented their diet with either maltodextrin (MD) or oligofructose (OF) 7g twice daily. Fasted assessments performed pre- and post-diet included MRI to assess colonic volume, breath testing for hydrogen and methane, and stool collection for microbiota analysis. Results The low FODMAP diet was associated with a reduction in Bifidobacterium and breath hydrogen, which was reversed by oligofructose supplementation. The difference in breath hydrogen between groups post-intervention was 27ppm (95% CI 7 to 50, P<0.01). Colonic volume increased significantly from baseline in both groups (OF increased 110ml (19.6%), 95% CI 30ml to 190ml, P = 0.01; MD increased 90ml (15.5%), 95% CI 6ml to 175ml, P = 0.04) with no significant difference between them. Colonic volumes correlated with total breath hydrogen + methane. A divergence in Clostridiales abundance was observed with increased abundance of Ruminococcaceae in the maltodextrin group, while in the oligofructose group, Lachnospiraceae decreased. Subjects in either group with high methane production also tended to have high microbial diversity, high colonic volume and greater abundance of methanogens. Conclusion A low FODMAP diet reduces total bacterial count and gas production with little effect on colonic volume.